Implementasi Metode Weighted Product untuk Rekomendasi Tempat Makan Halal di Bali (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2023)
The growing tourism industry in Bali must be responded to by improving service facilities for tourists, so that Bali remains popular with many people. Including providing facilities to show the location of halal dinning places according to the criteria required by the user. Also considering that current technological developments can be easily accessed by many people, for some of these reasons the authors in this study intend to create an information system by implementing the weighted product method in order to provide recommendations for halal places to eat according to the criteria required by users. The results of this study are a recommendation system for halal places to eat in Bali on website and mobile platforms, with a recommendation accuracy of 90% based on the results of accuracy testing and error values.